2013
DOI: 10.1089/ees.2013.0164
|View full text |Cite
|
Sign up to set email alerts
|

Improving Neural Network Prediction Accuracy for PM10 Individual Air Quality Index Pollution Levels

Abstract: Fugitive dust deriving from construction sites is a serious local source of particulate matter (PM) that leads to air pollution in cities undergoing rapid urbanization in China. In spite of this fact, no study has yet been published relating to prediction of high levels of PM with diameters < 10 lm (PM 10 ) as adjudicated by the Individual Air Quality Index (IAQI) on fugitive dust from nearby construction sites. To combat this problem, the Construction Influence Index (Ci) is introduced in this article to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…The time series data were decomposed into wavelet functions, and wavelet coeicients were predicted. All three models were found to give similar results, and when CI was included, the model gave improved predictions for peaks in PM 10 concentration [54].…”
Section: Explanatory Variablesmentioning
confidence: 71%
“…The time series data were decomposed into wavelet functions, and wavelet coeicients were predicted. All three models were found to give similar results, and when CI was included, the model gave improved predictions for peaks in PM 10 concentration [54].…”
Section: Explanatory Variablesmentioning
confidence: 71%
“… 45 Study conducted in China showed that fugitive dust deriving from construction sites is a serious local source of PM 2.5 that leads to air pollution in cities undergoing rapid urbanization. 46 Moreover, study conducted in Nepal shown that overall average PM 2.5 concentrations and peak 1 hour CO concentrations exceeded WHO Indoor Air Quality Guidelines. 47 …”
Section: Discussionmentioning
confidence: 98%
“…Hava kalitesi indeksi (HKİ), hava kirliliğine bağlı sağlık riski düzeyini ifade etmek için kullanılan bir terim olup, hava kalitesini basit ve anlaşılabilir bir şekilde açıklamaktadır [22,24]. HKİ, insan sağlığına ilişkin olarak farklı bileşenlerin hava kalitesi hakkında düzgün bir şekilde rapor vermek için kullanılan kantitatif bir ölçüdür [23]. HKİ değeri, bir bölgedeki her bir kirletici için ayrı ayrı hesaplanır ve her bir kirletici için hesaplanan en yüksek HKİ, o güne ait HKİ değerini oluşturmaktadır [24].…”
Section: Hki̇ Hesaplama Yöntemiunclassified